2001
DOI: 10.1046/j.1525-1594.2001.025003213.x
|View full text |Cite
|
Sign up to set email alerts
|

A Honeycomb Collagen Carrier for Cell Culture as a Tissue Engineering Scaffold

Abstract: As a three-dimensional carrier for cell culture, a honeycomb structure cell scaffold was created from atelopeptide collagen Types I, II, and III. The diameter of the honeycomb pores ranged from 100 to 1,000 microm. The depth of the pores was from 10 to 3,000 mm. The scaffold was elastic and hard. Creation of various shapes was easy, and these shapes were easily maintained. Human fibroblasts, CHO-K1, BHK-21, and bovine endothelial cells were cultured with the scaffold. The growth curves of these cells were sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 15 publications
2
65
0
1
Order By: Relevance
“…Among the widely used natural biopolymers, collagen has been conventionally applied in the clinic in various forms, such as gels or sponges, since it shows good biocompatibility and absorbability. Atelocollagen molecules do not contain telopeptides, and show extremely low antigenicity when adopted as basic materials for medical use 16) . Schlegel et al 17) reported that transplantation of bovine collagen alone into mini-pig skull defects showed higher degrees of de novo bone formation comparable with that of autogenous bone grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Among the widely used natural biopolymers, collagen has been conventionally applied in the clinic in various forms, such as gels or sponges, since it shows good biocompatibility and absorbability. Atelocollagen molecules do not contain telopeptides, and show extremely low antigenicity when adopted as basic materials for medical use 16) . Schlegel et al 17) reported that transplantation of bovine collagen alone into mini-pig skull defects showed higher degrees of de novo bone formation comparable with that of autogenous bone grafts.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] . We selected atelocollagen honeycomb scaffold as a carrier, because it offers a good environment for the cells and good mechanical stability, and maintains its original size and shape during cell growth in vitro 17) . Importantly, KUSA/A1 cells on Atelocollagen scaffold were able to proliferate and differentiate into osteoblasts, followed by the degradation of the scaffold.…”
Section: Quantification Of Bone Induction Vessel Formation and Cellumentioning
confidence: 99%
“…It is even used to minimize allergic reactions in cosmetics 16) . In the present study, we selected atelocollagen type I honeycomb scaffold because it has high cell affinity, and maintains its structural integrity, original size and shape during cell growth in vitro 17) .…”
Section: Introductionmentioning
confidence: 99%
“…Collagen sponges are considered to be a useful scaffold matrix for several tissues. And extra cellular matrix molecules such as laminin and fibronectin can be adsorbed onto the collagen scaffold, in order to aid cell migration and proliferation 9) . Furthermore, Type I collagen is the major component of the bone matrix and is useful as a carrier of osteoblasts 10) .…”
Section: Discussionmentioning
confidence: 99%